Understanding the Consequences of Toxic Leadership in the Business Sector: An Empirical Study in Saudi Arabia - El-Shafie, Elham; A. Nassani, Abdelmohsen; Aljumah, Gadah (The Arab Journal of Administration, 2025)
Toxic leadership behavior has garnered increasing attention in organizational research due to its detrimental effects on employee well-being and organizational performance. The purpose of the study is to investigate the consequences of toxic leadership in Saudi Arabia and aims to find the relation that exists between 8 constructs: toxic leadership and organization trust, toxic leadership and employee engagement, organization trust and job satisfaction, organization trust and organization commitment, organization trust and employee engagement, employee engagement and job satisfaction, employee engagement and organization commitment, job satisfaction, and organization commitment. The research was conducted in the labor market of Saudi Arabia, encompassing both the public sectors and private sectors. The research uses A web-based questionnaire with 211 respondents was used to collect data, and data was analyzed through SPSS and AMOS. The results of the study show that toxic leadership has an inverse relationship with organizational trust and employee engagement, job satisfaction, and organizational commitment.